Mechanical and structural peculiarities of tibia shaft nonunion and its influence for treatment - Popsuishapka, Olexii; Lytvyshko, Valerii; Pidgaiska, Olga; Ashukina, Nataliya; Nesvit, Kateryna; Maltseva, Valentyna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. To study internal tensions in bone and soft tissues of shin at normal condition and at isolated tibia nonunion, the range of fragments displacement, callous structure and to sustain the conception of treatment. Methods. Due to finite element method we created three models: I — anatomic norm; II — transverse defect of 5 mm height on the middle-lower 1/3 border filled with collagen, III — as the second model with empty fibula defect of 10 mm height on the same level 2/3–1/3 border. In 45 patients with tibia shaft nonunion (term 4–18 months) we made resection of fibula fragment 10–15 mm on the same level of tibia nonunion with apparatus of external fixation. We studied the linear bone fragments displacement and callous structure. Results. At the axial loading in normal condition (I model) there was asymmetry of tensions in the lower part of shin bones on the lateral and medial sides. At the II model vertical tensions in the lower part of tibia decreased on the medial side up to 69 % and on the lateral side — up to 44 %, tensions increased in 5 times on the lateral side of fibula. The tangential stresses increased 3 times, their resulting force vector changed the outward direction and increased 7 times. In the III model tension distribution on the tibia surface became close to normal situation. In case of tibia nonunion there was fibrous-cartilages tissues, appeared because of transverse tensions. Patients walked with weight bearing from the first days after surgery, in 95.6 % bone fragments consolidation happened in 3.5–4 months. Conclusion. Excluding of fibula from bearing function due to its 10–15 mm resection on the level of nonunion will normalize the vector of loading in the tibia fragments and fibrous-cartilage regenerate and leads to it ossification.